Targeting Ferroptosis Attenuates Interstitial Inflammation and Kidney Fibrosis - Lu Zhou; Xian Xue; Qing Hou; Chunsun Dai (Karger Publishers, 2021)
Background: Ferroptosis, an iron-dependent form of regulated necrosis mediated by lipid peroxidation, predominantly polyunsaturated fatty acids, is involved in postischemic and toxic kidney injury. However, the role and mechanisms for tubular epithelial cell (TEC) ferroptosis in kidney fibrosis remain largely unknown. Objectives: The aim of the study was to decipher the role and mechanisms for TEC ferroptosis in kidney fibrosis. Methods: Mouse models with unilateral ureter obstruction (UUO) or ischemia/reperfusion injury (IRI) were generated. Results: We found that TEC ferroptosis exhibited as reduced glutathione peroxidase 4 (GPX4) expression and increased 4-hydroxynonenal abundance was appeared in kidneys from chronic kidney disease (CKD) patients and mouse models with UUO or IRI. Inhibition of ferroptosis could largely mitigate kidney injury, interstitial fibrosis, and inflammatory cell accumulation in mice after UUO or IRI. Additionally, treatment of TECs with (1S,3R)-RSL-3, an inhibitor of GPX4, could enhance cell ferroptosis and recruit macrophages. Furthermore, inhibiting TEC ferroptosis reduced monocyte chemotactic protein 1 (MCP-1) secretion and macrophage chemotaxis. Conclusions: This study uncovers that TEC ferroptosis may promote interstitial fibrosis and inflammation, and targeting ferroptosis may shine a light on protecting against kidney fibrosis in patients with CKDs.